Biochemical and structural characterisation of a haloalkane dehalogenase from a marine Rhodobacteraceae. Issue 9 (5th March 2014) - Novak, Halina R.; Sayer, Christopher; Isupov, Michail N.; Gotz, Dorothee; Spragg, Andrew Mearns; Littlechild, Jennifer A.
Abstract : A putative haloalkane dehalogenase has been identified in a marine Rhodobacteraceae and subsequently cloned and over‐expressed in Escherichia coli . The enzyme has highest activity towards the substrates 1, 6‐dichlorohexane, 1‐bromooctane, 1, 3‐dibromopropane and 1‐bromohexane. The crystal structures of the enzyme in the native and product bound forms reveal a large hydrophobic active site cavity. A deeper substrate binding pocket defines the enzyme preference towards substrates with longer carbon chains. Arg136 at the bottom of the substrate pocket is positioned to bind the distal halogen group of extended di‐halogenated substrates. Abstract : Isolation of a marine Rhodobacteraceae sp. from a tube worm. Identification of a putative haloalkane dehalogenase enzyme. Characterisation and crystal structure of the native haloalkane dehalogenase enzyme and product bound complex. Relationship between the substrate specificity and the size and charge distribution within the active site cavity.